(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى قياس التّنوع السلعي للصادرات السورية إلى دول مجلس التعاون الخليجي باستخدام مؤشر هيرفندل –هيرشمان، وكذلك قياس التركز الجغرافي للصادرات السورية باستخدام المؤشر نفسه، كما يهدف إلى قياس المزايا النسبية لهذه الصادرات خلال العقدين الماضيين. وقد توصل البحث إلى جملة من النتائج أهمها: • تتركز الصادرات السلعية الغذائية إلى دول المجلس في الخضار والفواكه والحيوانات الحية. • تتركز الصادرات جغرافيا في السعودية. • فقدان سوق دول المجلس للصادرات النسيجية. كما توصل البحث إلى التوصية بضرورة الاهتمام بزيادة مكونات السلة السلعية المصدرة إلى دول الخليج والاهتمام بالتركيز على تصدير السلع التي تتضمن قيماً مضافة أكبر، والعمل على استعادة السوق الخليجية للصادرات النسيجية، وتقليص العقبات التي تواجهها الصادرات السورية أثناء دخولها دول المجلس، وخصوصاً أثناء دخولها إلى السوق السعودية. Using Herfend-Hershmans indicator, this research aims at measuring the diversity of the Syrian goods as well as measuring the geographical concentration of the Syria exports according to the same indicator. It also aims at measuring the comparative advantages of the export s during the past of three decades. The research has come to a number of outcomes. The most important of which are: • The foodstuff export to the council states consists mostly of vegetables and fruits. • Geographically, the exports are concentrated mainly in saudi arabia. • The absence of the Gulf market with regard to the textile export. The research also recommended that it is necessary to divesify exports to the gulf states, concentrating on exporting the goods which have more addition values; seeking to restore the Gulf market with regard to the textile exports, and finally reducing the obstacles standing in the way of Syrian exports when they are sent to the council states especially saudi arabia.